WRN Germline Mutation Is the Likely Inherited Etiology of Various Cancer Types in One Iranian Family - Norouzi, Mahnaz; Shafiei, Mohammad; Abdollahi, Zeinab; Miar, Paniz; Galehdari, Hamid; Emami, Mohammad Hasan; Zeinalian, Mehrdad; Tabatabaiefar, Mohammad Amin (Frontiers in Oncology, 2021)
Background: Familial cancers comprise a considerable distribution of colorectal cancers (CRC), of which however, only about 5% of them occurs through well-established hereditary syndromes. It has been demonstrated that deleterious variants at the newly identified cancer-predisposing genes could describe the etiology of undefined familial cancers. Methods: We conducted theThe present study aimed to identify the genetic etiology in a 32-year-old man with early-onset familial CRC employing several molecular diagnostic techniques. DNA was extracted from tumoral and normal formalin-fixed-paraffin-embedded (FFPE) blocks, and microsatellite instability (MSI) was evaluated. Immunohistochemistry staining of MMR proteins was performed on tumoral FFPE blocks. Next-generation sequencing (NGS), multiplex ligation-dependent amplification (MLPA) assay, and Sanger sequencing were applied on the genomic DNA extracted from peripheral blood. Data analysis was performed using bioinformatics tools. Genetic variants interpretation was based on ACMG. Results: MSI analysis indicated MSI-H phenotype, and IHC staining proved no expressions of MSH2 and MSH6 proteins. MLPA and NGS data did not showed no pathogenic variants in MMR genes. Further analysis of NGS data revealed a candidate WRN frameshift variant (p.R389Efs*3), which was validated with Sanger sequencing. The variant was interpreted as pathogenic since it met the criteria based on the ACMG guideline including very strong (PVS1), strong (PS3), and moderate (PM2). Conclusion: WRN is a DNA helicase participating that participates in DNA repair pathways to sustain genomic stability. WRN deficient function might may contribute to CRC development that is valuable for further investigation as a candidate gene in hereditary cancer syndrome diagnosis.